Ultrasound diagnosis of cervical levels II–IV lymph node metastasis in patients with first diagnosed papillary thyroid cancer - V. S. Parshin; A. A. Veselova; V. S. Medvedev; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи, 2020)
The study objective is to explore the potentialities of ultrasound in the detection of metastasis from papillary thyroid cancer (PTC) to cervical lymph nodes in levels II–IV.Materials and methods. In 97 patients with first diagnosed PTC, surgical removal of the cervical lymph node-bearing fat at levels II–IV was performed. All patients underwent preoperative neck ultrasound. The results were verified by histology.Results. Cervical levels II–IV lymph node metastases were revealed in 82 (84,5 %) cases by sonography and in 86 (88,6 %) cases by histology. Ultrasound showed a sensitivity of 93 %, specificity of 81 %, accuracy of 91 %, positive predictive value of 97 % and negative predictive value of 60 %. Of 1620 removed lymph nodes, 443 (27,3 %) showed metastases confirmed by histology. Sonography revealed 422 (26,0 %) metastatic lymph nodes. Metastasis from intra-thyroid tumors was noted in 94,1 % and from extra-thyroid tumors in 87,5 % of patients. Metastasis from solitary tumors occurred in 86,5 % and from multicentric tumors in 92,1 % of cases. Multiple metastases made up 89,5 % and solitary metastases – 10,5 %.Conclusion. Sonography is a highly informative diagnostic imaging method in detecting metastasis from PTC to levels II–IV cervical lymph nodes and can be used for basic assessment of thyroid abnormalities.